Strengthening Employee Performance Through Leadership Style and Work Environment Support at Drinking Water Companies - Mansyur, Herlin; Ikram , Muh.; Ahmad AC, Idrus (Manunggal Halim Jaya, 2024)
This research aims to analyze and explain the significant influence of the variables transformational leadership style, transactional leadership style, and work environment on employees of the Makassar City Regional Drinking Water Company. Employee discomfort at work can result in work being late. This disrupts the smooth implementation of the work of employees of the Makassar City Regional Drinking Water Company and indicates why employees lack enthusiasm for work and makes employee performance not optimal. The problem in this research is whether the transformational leadership style, transactional leadership style, and work environment have a significant influence on the employee performance of the Makassar City Regional Drinking Water Company. This type of research is quantitative research using questionnaires as a source of data collection. There were 86 participants in this research and were analyzed using a descriptive approach, validity and reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results of this research show that The transformational leadership style has a significant effect on employee performance. The stronger the transformational leadership style possessed by the leader, the more employee performance will increase. A transactional leadership style does not have a significant effect on employee performance. This shows that the higher the perception of the transactional leadership style, the lower employee performance will be. The work environment has a significant effect on employee performance. This shows that the better the work environment felt by employees, the more the quality of employee performance at the Makassar City Drinking Water Regional Public Company will improve.